Stylistic reflections on Surat Al-Qara'a (Journal of the College of Basic Education, 2023)
The specificity of the heavenly books, especially the Holy Qur’an, as a text distinguished by its chapters and verses, and the spirit of holiness spread within it, made it a sweet source for innovators. Tributaries of the innovator, for he is the one who challenged the Arabs with his statement and rhetoric  Say: If mankind and jinn gathered together to produce the like of this Qur’an, they would not produce the like of it, even if they backed each other up. You were honest. And because it is the impeccable discourse that combines the colors of speech, eloquence, and statement, the owner of the influential power in the souls, “and he preserved Arabic from loss, spread it in the countries of the earth, and made it alive and immortal.” As a lexicon rich in words that no author knows about, and a continuous meaning at all times, and indicates high and rich semantic capabilities, and accordingly, the Holy Qur’an is the main transformer for the establishment of an Arab civilization based on linguistics generated through controversy or human controversy with reality on the one hand, and the human relationship with the text and permanent dialogue or controversy. The existing one between him and his Creator on the other hand, and this is what made the Holy Qur’an constitute a very important and intertwined impact in all aspects and an important axis in the history of the Arab-Islamic civilization so that we find the breadth of authorship with regard to the Holy Qur’an and its sciences. Many of the sciences that were later known as the sciences of the Noble Qur’an, namely the interpretation, the arbitrator, the allegorical, the abrogated, the abrogated, and the causes of revelation.As for the study of the Qur’anic text and the analysis of its methods, it occupied a great position among Muslim scholars, even non-Muslims.